Pengaruh Model Pembelajaran Team Based Project terhadap Hasil Belajar Siswa pada Mata Pelajaran Gambar Teknik Manufaktur - Wira, Aski; Syahri, Budi; Adri, Junil; Putra, Randi Purnama (Jurnal Vokasi Mekanika (VoMek), 2025)
Most of the teaching and learning of Manufacturing Engineering Drawing is still teacher-centered. Learning with the conventional model previously used made students passive and not independent in their learning. As a result, students are unable to understand the basic concepts of CAD drawings, interpret drawings, and understand the function of tools found in AutoCAD tools. This makes student learning achievements far from the minimum graduation criteria set by SMKN 5 Padang. The use of the Team Based Project learning model in this research aims to see its effect on student learning outcomes. Cluster random sampling is a sampling technique. To collect data, a pretest was carried out before the two groups were given different treatments. After the treatment, a post-test and assessment of student performance was carried out. The results of the analysis show that there are significant differences in learning outcomes. The test results showed an average in the cognitive domain of 88.7 for the experimental class and 82.58 for the control class, in the psychomotor domain 81.76 for the experimental class and 74.11 for the control class. Then the sign value from the T-test and F-test results is <0.05. Therefore, it can be concluded that the use of the Team Based Project learning model has a significant influence on student learning outcomes in Manufacturing Engineering Drawing.